Nilai-Nilai Pendidikan Karakter dalam Buku Habis Gelap Terbitlah Terang - R.R. Sri Setyawati Mulyaningsih; Lalu Mas’Ud (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2022)
ABSTRACT The purpose of the study was to determine the factors behind R.A Kartini's thoughts and the values ​​of character education in the book After Dark Terbitlah Terang. The research method uses a document study content analysis approach with data in the form of documents that are analyzed using a hermeneutic approach. The results of the study show that the factors behind the birth of R.A Kartini's thoughts in his book are the marginalized educational conditions of women, Javanese society is still feudal and places women in a position that is considered weak, women are not free to appear in public and their education is limited. The values ​​of character education contained in it include; religious, unyielding, love to read, care, and tolerance. The five characters are the embodiment of 18 character values ​​according to the 2013 curriculum which focuses on moral and character education. The conclusion of this research is the condition of Javanese society and the condition of women's education at that time triggered the birth of Kartini's thoughts which eventually wrote the book After Dark Terbitlah Terang which is full of character education values. Keyword: Character Education, Habis Gelap Terbitlah Terang, Kartini